Short term neonatal outcomes of singleton term breech delivery: two year experiences in a Malaysian tertiary hospital - Abdul Hamid, Habibah; Mohd Jamil, Amilia Afzan; A., Fatin Amirah; Hong, Y.T.; Rejali, Zulida (Community Health Society Malaysia, 2016)
Background: There are few neonatal complications of breech delivery including the low Apgar score, birth trauma, admission to neonatal unit and perinatal mortality. Objective: To review the short term complications and their associating factors among singleton term breech infants in relation to mode of delivery. Methodology: This is a cross-sectional study that involves 294 term singleton pregnant women with breech presentation in Hospital Serdang, Malaysia from January 1, 2014 to December 31, 2015. Data abstracted from the delivery record book and the hospital database computerised system were used to compare the short term outcomes of singleton term breech infants born via vaginal breech delivery and pre-labour or in-labour caesarean section. Results: Out of 294 cases, 25% (n=73) displayed a successful vaginal delivery, whereas the remaining 75% (n=221) have undergone caesarean delivery. It was more common in multiparous women (64.3%) and frank-typed of breech (59.9%) is more prevalence compared to others. Nulliparity was found significantly predominant in caesarean section delivery (OR 2.38, 95% CI 1.114-5.084, p= 0.005), while the complete-typed of breech was significantly lesser in caesarean section group (OR 0.47, 95% CI 0.246-0.915, p= 0.026). However, there was no significant difference discovered in adverse neonatal outcome regarding the mode of delivery. Conclusion: Pre or in- labour caesarean section and vaginal delivery in terms of singleton breech presentation contains a similar risk of adverse neonatal outcome. According to this study, the main risk factors affecting the mode of delivery are parity and type of breech presentation.